The effects of static stretching warm-up versus dynamic warm-up on sprint swim performance - Moran, M.; Whitehead, J.; Guggenheimer, J.; Brinker, R. (Journal of Swimming Research, 2014)
Recent research has revealed that static stretching (SS) warm-ups may attenuate power performance compared to dynamic protocols, but most studies have focused on dry land modalities. This study examine d the effects of an SS warm-up versus a dynamic warm-up (DW) on freestyle sprint performance in competitive swimmers. Using a crossover design, 16 NCAA Division 1 swimmers swam a 50-meter freestyle sprint after two different warm-up protocols that were designed to mirror typical practice among competitive swimmers, while allowing any practically significant experimental effects from the SS versus DW contrasts to occur: Specifically, the warm-ups were Static Stretch + Swim (SS/S), and Dynamic Warm-up + Swim (DW/S). In each case the contrasting experimental warm-up exercises (nine static stretches versus nine dynamic movements) were immediately followed by a typical swimming warm-up (about 20 minutes). The timed 50-meter sprints took place 5-minutes after the SS/S and DW/S warm-ups, and they were conducted three days apart under simulated competitive conditions. In separate analyses there were no significant differences in mean times over the first 25 meters, the second 25 meters, or the overall 50-meter sprint time. Thus, in contrast to the effects shown in many other performance modalities, SS in warm-up did not attenuate performance in this study. It is possible that the swimming warm-up done subsequently to the SS or DW component may have blunted any SS-induced performance deficits . Thus, future research might vary the swimming component of warm-up to see if any effects of SS versus DW emerge.